1998
DOI: 10.1111/j.1744-6171.1998.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

“Sometimes You Don't Feel Ready to Be an Adult or a Mom:” The Experience of Adolescent Pregnancy

Abstract: The findings of this study indicate that for some adolescents, pregnancy implies a desire and an opportunity to heal childhood wounds if relevant psychotherapeutic interventions can be provided. Nurses can identify pregnant teens who are already suffering with depression and encourage them to seek counseling prior to the birth of their baby before they are experiencing the added stressors inherent in new motherhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 19 publications
(8 reference statements)
5
44
0
Order By: Relevance
“…Respondents still believed that they could not fall pregnant if they engaged in unprotected sexual intercourse. Only few respondents mentioned that they would like to get mar- ing and direct effects, social support is believed to ex ert a mediating influence on psychological well-being and maternal behaviours that may beneficially affect the developing mother-child relationship (Lesser et al 1998:12, Ponirakis, Susman & Stifter, 1998.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Respondents still believed that they could not fall pregnant if they engaged in unprotected sexual intercourse. Only few respondents mentioned that they would like to get mar- ing and direct effects, social support is believed to ex ert a mediating influence on psychological well-being and maternal behaviours that may beneficially affect the developing mother-child relationship (Lesser et al 1998:12, Ponirakis, Susman & Stifter, 1998.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…SmithBattle (2007b) found that pregnancy and parenting served as an impetus for new concerns and priorities about the future. Lesser, Anderson, and Koniak-Griffin's (1998) analysis of pregnant teens identified the theme of "reparation" as "the adolescents' desire to repair and heal the wounds they had suffered, often at the hands of their own parents, when they were younger" (p. 12). Lesser discusses the notion of "reparation" in pregnancy as a positive turning point in the lives of young mothers and a desire to heal a dysfunctional past (Lesser et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Lesser, Anderson, and Koniak-Griffin's (1998) analysis of pregnant teens identified the theme of "reparation" as "the adolescents' desire to repair and heal the wounds they had suffered, often at the hands of their own parents, when they were younger" (p. 12). Lesser discusses the notion of "reparation" in pregnancy as a positive turning point in the lives of young mothers and a desire to heal a dysfunctional past (Lesser et al, 1998). The women in Lesser and colleagues' study wished to repair the wounds of their own childhoods by providing an ideal life for their own children.…”
Section: Discussionmentioning
confidence: 99%
“…Responsibility, respect, and reparation characterized these adolescents' experience. For some adolescents, pregnancy provided an opportunity to heal past childhood wounds if appropriate psychological services were provided (Lesser et al, 1998). Paskiewicz (2001) found that communication, role change, conflict, and social isolation were characteristic of participants' experience in parenting and their relationship with their own mother or mother figure.…”
mentioning
confidence: 99%